The Meaning of Japuik Money Completers in the Marriage System in Tiku Region, Agam District - Wulanda Khairunisa; Elida Elida (Science and Environmental Journal for Postgraduate, 2021)
This study aimed to determine the meaning of accompanying japuik money in the marriage system in the Tiku region, Agam regency. This research was qualitative research with a descriptive type. The research informants were determined by convenience sampling. The results of this study indicated that the meanings of the means of accompanying japuik (pick-up) money were: a) Keris, which means male power in Minangkabau, b) Tigo rupo ring (copper, silver, and gold) means that in Minangkabau, one decision cannot be separated from the deliberation of Tigo Tungku Sajarangan (Alim Ulama, Cadiak Pandai, Panghulu), c) Betel, Lime, Gambir, Pinang, Tobacco mean that in Minangkabau a decision is solid and must live in deliberation and be aware of the surrounding environment, d) Salapah Tunsi means determining whether the prospective bride is still virgin or not. The conclusion is that the japuik money is not merely giving a certain amount of money, but there is a special meaning behind the japuik money.